PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN ARTICULATE STORYLINE DENGAN MODEL PBL UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SECARA HOTS PADA IPAS SEKOLAH DASAR - Ayu Az Zahra, Dellayla; Isdaryanti, Barokah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The focus of this research is to develop learning media based on Articulate Storyline with PBL model for social studies content IPAS lessons grade IV at SD Negeri Tambakaji 03. This research and development method uses ADDIE model development research. Problems identified in the research include students' difficulty in understanding complex material, difficulty understanding important terms, and low ability of students to follow HOTS learning. The media created was then tested by experts for feasibility, with the results of 92.85% feasible according to material experts, 94.56% feasible according to media experts, and 98% feasible according to classroom teachers. In addition, this media showed significant results in the T-test of 0.000602 and the N-gain test of 70.16%, which means that the media is effective in improving learning outcomes.